2018
DOI: 10.7196/ajhpe.2018.v10i2.988
|View full text |Cite
|
Sign up to set email alerts
|

Establishing consensus among interprofessional faculty on a genderbased violence curriculum in medical schools in Nigeria: A Delphi study

Abstract: There is growing international consensus that health services need to respond to the needs of those experiencing abuse. [1] There is also an increasing recognition of the need to equip medical practitioners with the appropriate knowledge, attitudes and skills to care for victims of intimate partner violence (IPV). Concerns have been raised that faculty possibly neglect teaching of the topic, as it is not included in medical curricula. [2] It is therefore imperative to address this shortcoming in medical curric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Using the Delphi technique, Fawole et al [7] sought to obtain consensus from teachers on a gender-based violence curriculum for medical schools in Nigeria. The study identified topics for inclusion, level of study at which the curriculum should be taught, methods of teaching and who should teach.…”
Section: Editorialmentioning
confidence: 99%
“…Using the Delphi technique, Fawole et al [7] sought to obtain consensus from teachers on a gender-based violence curriculum for medical schools in Nigeria. The study identified topics for inclusion, level of study at which the curriculum should be taught, methods of teaching and who should teach.…”
Section: Editorialmentioning
confidence: 99%